(untitled) (Revista Latino-Americana de Enfermagem, 2002)
The purposes of this study were to assess the health habits related to risk factors in hospitalized hypertensive patients and to identify these patients' knowledge on the importance of controlling these factors. Thirty two hypertensive patients hospitalized at a University Hospital were interviewed. Although these patients mentioned that they controlled the risk factors for hypertension and that they knew about the importance of this control, a high blood pressure was observed even during hospitalization and the majority of them presented damage in target organs. There is a need to search for educative measures that will enable a change in the life style of these patients, encouraging them to control the risk factors and the evolution of the disease.